Mental health service delivery among adolescent girls and young women (AGYW) seeking HIV prevention and treatment services in central Kenya: A qualitative study of AGYW and healthcare providers’ perceptions - Emmah Owidi; Kenneth Ngure; Peter Mogere; John Njoroge; Snaidah Ayub; Roy Njiru; Boaz Kipkorir; Edinah Casmir; Catherine Kiptinness; Tessa Concepcion; Tamara Owens; Pamela Kohler; et al. (PLoS ONE, 2025)
Introduction Common mental disorders (CMDs) are prevalent among adolescent girls and young women (AGYW) in high HIV-burden settings. However, mental health is underprioritized within HIV interventions targeting AGYW. We conducted a qualitative study to explore AGYW and healthcare providers’ perceptions of mental health service delivery within HIV clinics. Methods Between 16th February and 14th June 2021, we conducted in-depth interviews with AGYW receiving HIV services and healthcare providers from eight clinics in Central Kenya. Eligible AGYW were aged 16–25 years and reported mild-to-moderate CMD symptoms, determined by the Self-Reporting Questionnaire 20-item (SRQ-20) mental health screening tool. Eligible providers currently provided HIV or mental health services. Interviews explored AGYW’s experiences with CMDs and factors influencing mental health service delivery by providers within HIV clinics. We analyzed data deductively and inductively using thematic analysis and organized findings using the socio-ecological model. Results Median age among AGYW (n = 20) was 21 years (IQR:18–24), and SRQ-20 screening score was 9 (IQR: 8–11). Providers (n = 10) comprised seven females; and included six HIV and four mental healthcare providers. AGYW described experiences of CMDs due to multi-level risk factors, including HIV stigma, financial problems, and relationship challenges. AGYW reported a high demand for mental health services but described a systemic lack of access. Convenience and positive experiences with providers facilitated AGYW’s access to services. Conversely, HIV care providers felt less confident in delivering mental health services due to inadequate mental health training compared to mental healthcare providers. Providers also reported inadequate training, poor referral systems, and unclear guidelines that hindered service delivery. AGYW and providers endorsed mental health service integration within HIV clinics to potentially reduce referral burden for AGYW and improve service quality. Conclusions Our findings highlight gaps in mental health service delivery among AGYW receiving HIV services. Integrated service delivery within HIV clinics could improve AGYW’s access to mental health services.